Neurobehavioral, Neuromotor, and Neurocognitive Effects in Agricultural Workers and Their Children Exposed to Pyrethroid Pesticides: A Review - Lucero, Boris; Muñoz-Quezada, María Teresa (Frontiers in Human Neuroscience, 2021)
In recent years, pyrethroids have emerged as a less toxic alternative to eliminate insect pests. However, some animal studies and studies with children show that these pesticides are toxic and lead to neurobehavioral effects similar to other pesticides, such as organophosphates. The purpose of this review was to systematize the epidemiological scientific evidence about the neurobehavioral, neuromotor, and neurocognitive effects in agricultural workers and their children exposed to pyrethroid pesticides. We conducted two searches (with different terms) in PubMed and Scopus databases, including articles in Spanish and English language on the effects of occupational exposure to pyrethroid pesticides associated with neurobehavioral, neuromotor, and neurocognitive functioning of agricultural workers and their children. There were no filters by year, and the search included studies till march 2021. To develop the search, we followed the recommendations contained in the PRISMA guidelines and the PICO strategy. The results show that in 66.6% of the studies reviewed (8 of 12 studies), agricultural workers or their children occupationally exposed to pyrethroid pesticides have a higher risk of presenting difficulties in their neurocognitive, neuromotor, or neurobehavioral performance, mainly associated with attention, processing speed (linked to hand-eye coordination), and motor coordination. There are still few studies that address this issue. However, the quality of most of the research conducted (83% intermediate or high quality) confirms the risk for neurobehavioral health in agricultural workers due to occupational exposure to pyrethroids. More research is required evaluating the exposure to pyrethroids, including biomarkers and validated neurobehavioral and neuromotor tests, in addition to evaluating the effect of simultaneous exposure to other hazardous pesticides. Assuming that the use of pyrethroids is increasing considerably and faster than the scientific evidence, it is suggested as a precautionary principle to regulate, more strictly, the sale of pyrethroids and other pesticides.